(untitled) (Research, Society and Development, 2021)
The aim of the present study was to evaluate pain in oncology patients and the way in which the multidisciplinary team has been taking care of this difficult symptom. The study is a literature review tipe. The results presented were in relation to cancer pain, in the presence of signs and symptoms of difficult control, the Nurse plays a fundamental role in relieving the discomfort and suffering of the same, because it assists the patient during the 24 hours and accompanies the aspects and is a of the concerns most present in the day-to-day of the nurse who works with this type of patient, mainly in the palliative care units. Palliative care is understood to mean all active and global care given to a patient whose illness has not responded to curative treatment; however, in order to provide such care, it is essential that the practitioner develops holistic knowledge about pain and, through it, achieves conditions to assess and size its complexity, it is understood that nursing is an irreplaceable profession when caring for society, how much its human practice is odd in the patient’s health. In this context, the need for alternative and complementary therapeutic techniques to conventional pain management is observed, but it does not require treatment with the drugs according to the medical guidelines for a satisfactory result.